Carriage of Staphylococcus aureus in Thika Level 5 Hospital, Kenya: a cross-sectional study - Aiken, Alexander M (BioMed Central, 2014)
BACKGROUND: Methicillin-resistant Staphylococcus aureus (MRSA) is an important nosocomial pathogen but little is known about its circulation in hospitals in developing countries. We aimed to describe carriage of S.aureus amongst inpatients in a mid-sized Kenyan government hospital. METHODS: We determined the frequency of S.aureus and MRSA carriage amongst inpatients in Thika Hospital, Kenya by means of repeated cross-sectional ward surveys. For all S.aureus isolates, we performed antibiotic susceptibility tests, genomic profiling using a DNA microarray and spa typing and MLST. RESULTS: In this typical mid-sized Kenyan Government hospital, we performed 950 screens for current carriage of S.aureus amongst inpatients over a four month period. We detected S.aureus carriage (either MSSA or MRSA) in 8.9% (85/950; 95%CI 7.1-10.8) of inpatient screens, but patients with multiple screens were more likely have detection of carriage. MRSA carriage was rare amongst S.aureus strains carried by hospital inpatients – only 7.0% (6/86; 95%CI 1.5-12.5%) of all isolates were MRSA. Most MRSA (5/6) were obtained from burns patients with prolonged admissions, who only represented a small proportion of the inpatient population. All MRSA strains were of the same clone (MLST ST239; spa type t037) with concurrent resistance to multiple antibiotic classes. MSSA isolates were diverse and rarely expressed antibiotic resistance except against benzyl-penicillin and co-trimoxazole. CONCLUSIONS: Although carriage rates for S.aureus and the MRSA prevalence in this Kenyan hospital were both low, burns patient were identified as a high risk group for carriage. The high frequency of genetically indistinguishable isolates suggests that there was local transmission of both MRSA and MSSA.